'Copyright Work and its Definition with Regard to Originality and AI' – Conference Report on the Fourth Binational Seminar of TU Dresden and Charles University in Prague, 27 June 2019. Issue 1 (8th January 2020) - Linke, David; Petrlík, David
Abstract: Bill Gates once wrote 'I am in the camp that is concerned about super intelligence' and positioned himself on the question of Artificial Intelligence. 1 Mr Gates was, however, concerned about the future of AI in order to be able to supply not only intelligent but also exceptional products. Following the third binational seminar in November 2018 on the topic 'Software and Artificial Intelligence – Old and New Challenges for Patent Law', 2 colleagues from the IGETeM, TU Dresden and Charles University in Prague met in Dresden on 27 June 2019 to focus on this question from the perspective of copyright. They also dealt with other current issues involving copyright, such as definition of work and the notion of originality.